Avaliação da sensibilidade insulínica, transdução do sinal insulínico e da densidade mineral óssea em ratas tratadas com fluoreto de sódio - Nunes, Rita de Cássia Alves [UNESP] (2014)
Osteoporosis is defined as a systemic disease characterized by bone degradation microarchitectonic and decreased bone mass, which promotes increased bone fragility and eventual fracture risk. Several studies have investigated the use of sodium fluoride (NaF) in the treatment for osteoporosis. Fluoride when ingested can accumulate in calcified tissues such as teeth and bones and may alter the quality of these tissues. Besides influencing bone metabolism, fluoride can also alter glucose homeostasis. Studies in rats have shown that chronic treatment with NaF (20 mg/L) in the drinking water has promoted the reduction in insulin signaling, and insulin resistance. Researches indicate the developing of a new endocrine axis involving the bones and glucose metabolism, and this opens a perspective of therapeutic options for the treatment of several pathologies. Therefore the aim of the study was to evaluate the effect of water intake with sodium fluoride at a dose of 50 mg/L in ovariectomized rats: 1) tyrosine phosphorylation status of insulin receptor substrate (pp185 - IRS-1 / IRS- 2) in white adipose tissue (WAT); 2) plasma glucose, insulin, cholesterols, triglyceride, TNF-, IL-6, calcium, fluoride and osteocalcin; 3) bone density and biomechanical properties (stiffness, maximum force and toughness) in the tibia; 4) tibia histomorphometric analysis. Fourty-two female Wistar rats (two months old) were ovariectomized and randomly distributed into two groups: 1) control (OVX-C), which was subjected to the treatment without NaF group but with a solution of NaCl (9.54 mg/kg bw) containing the same amount of sodium in relation to the NaF group; 2) NaF group (OVX-F) which was subjected to treatment with NaF (50 mg/L) administered in drinking water for 42 days. After this period, the following evaluations were carried out: 1) tyrosine...